(untitled) (Revista Argentina de Cirugía, 2022)
Garengeot’s hernia is defined as the presence of an appendix in the femoral hernial sac. We report the case of a 50 -year-old woman who presented with acute appendicitis within an incarcerated femoral hernia trated in two stages combined procederes: laparoscopic apendectomy first and open repair of the femoral hernia once week later. When the appendix is inflamed the two stages combined procederes avoid the fixation of the mesh in a contaminate place.